WORDWALL SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN MOTIVASI BELAJAR BAHASA INGGRIS SISWA SDN 39 PALEMBANG - Najlatul Fathia; Ilham Arya Susanto; Budiansyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the use of Wordwall as an interactive learning media in improving students’ motivation in learning English at SDN 39 Palembang. The research employed a qualitative approach with a descriptive qualitative design. The subjects of this study were 10 teachers at SDN 39 Palembang selected through purposive sampling technique. Data were collected through interviews, observations, and documentation. The data were analyzed using the Miles and Huberman interactive analysis model, including data reduction, data display, and conclusion drawing. The findings revealed that the use of Wordwall significantly improved students’ motivation in learning English. This was indicated by students’ high enthusiasm during the learning process, increased confidence in asking and answering questions, and a more interactive and enjoyable classroom atmosphere. In addition, Wordwall helped students understand English materials more easily and increased their self-confidence during the learning activities. Therefore, Wordwall can be considered an effective interactive learning media to enhance elementary school students’ motivation in learning English.